THE PENGARUH LITERASI KEUANGAN DIGITAL TERHADAP KESEJAHTERAAN KEUANGAN MELALUI PERILAKU PENGELUARAN, MENABUNG DAN INVESTASI DI INDONESIA - Benny Jhonson; Rike Andriani; Irma Noviana; Dewi Tamara (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
This study aims to determine if spending, saving, and investment behavior, via the mediation of digital financial literacy (DFL), influences Indonesians' financial well-being (FWB). An online survey with a sample size of 403 participants received a 77% response rate. The Structural Equation Model using SmartPLS showed that DFL influences FWB by mediating spending, saving, and investment behavior. Based on this result, the government is suggested to improve the level of DFL in Indonesian people through an educational curriculum that can pay attention to spending, saving, and investment behavior to maximize FWB.